Strategi Pemberdayaan Masyarakat oleh Kepala Desa dalam Pengembangan Kawasan Pariwisata Desa Tetebatu Selatan Kabupaten Lombok Timur Nusa Tenggara Barat - Indriani; Arwin Sanjaya (Jurnal Kajian dan Terapan Pariwisata, 2022)
This study aims to determine the strategy of the Village Head in community empowerment and to find out how the development of tourism areas in Tetebatu Selatan Village, East Lombok Regency, West Nusa Tenggara. This type of research is descriptive qualitative research. At the stage of formulating a tourism development strategy in the village of South Tetebatu, researchers used a SWOT analysis technique. The results of this study can be concluded that the community empowerment strategy in the development of tourism areas shows that the South Tetebatu village has tourism potential that can be developed further. Then, the potential analysis based on the aspects or criteria of the tourism village shows that of the seven aspects, only the readiness of community human resources and aspects of tourism support facilities still need to be improved, while the other five aspects, namely tourist attraction, community motivation, facilities and infrastructure, institutions and the availability of land, in general, are adequate to become a tourist village. In addition, tourism development in the village of South Tetebatu is quite good, it's just that there is a need for improvement so that in the future the village of South Tetebatu can become one of the best tourist villages in Indonesia.